Limit C^*-algebras associated with an automorphism - Solel, Baruch (Mathematica Scandinavica, 2004)
We present and study C^*-algebras generated by "periodic weighted creation operators" on the Fock space associated with an automorphism α on a C^*-algebra A. These algebras can be viewed as generalized Bunce-Deddens algebras associated with the automorphism and can be written as a certain direct limit. We prove a crossed product presentation for such an algebra and find a necessary and sufficient condition for it to be simple. In the case where the automorphism is induced by an irrational rotation (on C(T)) we compute the K-theory groups and obtain a complete classification of these algebras.